Deterrence Strategy Through Deploying KRI in the North Natuna Sea to Support the National Defense System - Cahyo Wibowo; Buddy Suseto; Harjo Susmoro (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The vast maritime territory of Indonesia, rich in natural resources, has attracted interest from various parties, both domestic and international, to exploit its potential, even if it means violating established regulations at the national and international levels. One of the maritime areas facing complex challenges, considering the numerous legal violations and threats to the sovereignty of the Republic of Indonesia (NKRI), is the North Natuna Sea. The objective of this research is to analyze the operational patterns and preparations patterns of the Indonesian Navy Vessels (KRI) for deterrence strategies in supporting the national defense system. This study employs a qualitative method, utilizing interviews as a research instrument, supported by literature reviews, including books and other written references related to the research object. The results of this research indicate that the deterrence strategy has not been optimally implemented. This is due to various encountered challenges in the efforts made, highlighting the need for evaluation and improvement of both operational and preparedness patterns of KRI. This is essential to ensure that the deterrence strategy in the North Natuna Sea region, supporting the national defense system, can be carried out effectively and efficiently.